2019
DOI: 10.3991/ijep.v9i3.9491
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Discussions to Develop the Entrepreneurial Mindset in Environmental Engineering Undergraduates: A Case Study

Abstract: Entrepreneurship is an important aspect of the U.S. and global economy. As such, developing an entrepreneurial mindset is crucial for both engineering students and practicing engineers. The purpose of this paper is investigate the role of online discussions, as a pedagogical approach, in the development of the entrepreneurial mindset, and explore a variety of approaches to assess student learning outcomes. Online discussions prompts were created for environmental engineering courses using the Kern Engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Online learning has a positive correlation with student attitude, in which they like it, but it does not influence assessment results (Wong & Fong, 2014). The online discussion gives students essential time to create a response that stimulates thinking, encourages students to consider information to support each other in posting their discussion (Bosman et al, 2019;Salehudin, Hamid et al, 2020). E-learning is more efficient when all teaching and learning approaches are applied.…”
Section: Discussionmentioning
confidence: 99%
“…Online learning has a positive correlation with student attitude, in which they like it, but it does not influence assessment results (Wong & Fong, 2014). The online discussion gives students essential time to create a response that stimulates thinking, encourages students to consider information to support each other in posting their discussion (Bosman et al, 2019;Salehudin, Hamid et al, 2020). E-learning is more efficient when all teaching and learning approaches are applied.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies reported that the inclusion of multiple blended components in a single course without proper alignment (to pedagogies or assessments) can increase the cognitive load on students [16]. Students collaborating on blended learning platforms have reported a lack of trust while working with peers or team members, especially when they have insufficiently frequent face-to-face interactions [25]. It is therefore important to ensure that the structure of a course incorporating blended learning aligns well with the other blended and non-blended components of the course.…”
Section: Benefits and Challenges Of Abc Learning Environmentsmentioning
confidence: 99%
“…While most of the aforementioned studies reported the benefits and challenges of the individual dimensions of ABC learning environments or a combination of active and collaborative learning [26] or blended and collaborative learning [27] [28] [25], new challenges may arise when one simultaneously combines the ABC learning environments, making their implementation complex. This may explain the lack of wide-spread development and simultaneous adoption of ABC learning environments in core STEM courses.…”
Section: Benefits and Challenges Of Abc Learning Environmentsmentioning
confidence: 99%
“…Обучение предпринимательству стало темой первостепенной важности в политике зарубежных технических университетов, при этом предпринимательская деятельность трактуется и как важный аспект мировой экономики [27], и как движущая сила инноваций [28]. Соответствующие навыки помогают превращать идеи в продукты.…”
Section: инновации в содержании образовательных программ высшегоunclassified